2003
DOI: 10.1034/j.1600-0722.2003.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of marginal and internal adaptation after occlusal stressing of indirect class II composite restorations with different resinous bases

Abstract: Composite inlays are indicated for large cavities, which frequently extend cervically into dentin. The purpose of this study was to compare in vitro the marginal and internal adaptation of class II fine hybrid composite inlays (Herculite, Kerr) made with or without composite bases, having different physical properties. Freshly extracted human molars were used for this study. The base extended up to the cervical margins on both sides and was made from Revolution (Kerr), Tetric flow (Vivadent), Dyract (Detrey-De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 25 publications
(25 reference statements)
2
52
1
2
Order By: Relevance
“…In the literature, larger proportions of enamel micro-fractures were observed in in-vitro mechanical loading tests conducted on cavities with a butt margin design [55,[57][58][59]. The parallel orientation of enamel prisms in the axial wall, in combination with the weakened region of non-bevelled enamel after phosphoric acid conditioning could be an explanation for these findings and may led to a reduction of marginal adaptation after TML.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, larger proportions of enamel micro-fractures were observed in in-vitro mechanical loading tests conducted on cavities with a butt margin design [55,[57][58][59]. The parallel orientation of enamel prisms in the axial wall, in combination with the weakened region of non-bevelled enamel after phosphoric acid conditioning could be an explanation for these findings and may led to a reduction of marginal adaptation after TML.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the elastic deformation of a more 'flexible' material (e-modulus lower than the restorative material) [4,22] placed close to or within the adhesive interface might help to absorb immediate (resin polymerization shrinkage) and delayed strains (spontaneous postpolymerization and functional forces). The importance of the elastic layer has been shown as early as 1990 [21,22]; since then, several studies confirmed the validity of this concept [10,12,40,42,43]. A last potential explanation for the inferior efficiency of such a one bottle adhesive is an insufficient or total lack of polymerization of the very thin resin layer left after adhesive placement and solvent evaporation (only a few microns) [44].…”
Section: Adaptation To Dentinmentioning
confidence: 72%
“…This very favourable finding likely reflects the influence of prism orientation in bonding efficiency to acidetched enamel; it is known that a bevelled margin with enamel prisms cut roughly perpendicular to their long axis is a configuration more favourable than a butt margin [18,39]. Actually, larger proportions of enamel micro-cracks were observed in in vitro mechanical loading tests conducted on cavities with a butt margin design [25,26,38,40]. This speaks again in favour of placing a bevel around cavities to be filled with a direct technique, wherever enamel thickness is 1 mm or more [41,58].…”
Section: Marginal Adaptation To Enamelmentioning
confidence: 99%
“…25,26 Since for the anterior vestibular restorations like composite veneers, the most relevant background is white, we also preferred to use white background in our study. 32 Resin composites used in dental restorations underwent color change when exposed to various storage media. The often-used solutions in research studies are coffee, black tea, red wine, coke, energy drinks, and some kind of soft beverages.…”
Section: Discussionmentioning
confidence: 99%